Identifikasi Kandungan Senyawa Kimia Cuka Kayu dari Sekam Padi - Nugrahaini, Dian Laila; Kusdiyantini, Endang; Tarwotjo, Udi; Prianto, A. Heru (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
Wood vinegar rice husk contains a chemical compound that can be used as a biopesticides. Wood vinegar contained compounds which estimated potential as repellent, antifeedant, antimicrobials, antioxidants, disinfectants and as preservatives. The content of chemical compounds in the wood vinegar must be identified. Identification were done by calculating the concentration of acid, phenol and an infrared spectrophotometer. Production of wood vinegar made by the pyrolysis process used pirolisator. Most of the wood vinegar obtained is evaporated using a rotary evaporator and partly extracted using the method of separating funnel. Compound of acid and phenol in wood vinegar evaporation were higher than the extraction of wood vinegar. These results were confirmed by an infrared spectrophotometer spectrum showed the functional groups of acid and phenolic compounds.Â Keywords: wood vinegar rice husk, acid, phenol, pyrolysis, infrared spetrofotometer